Photovoltaic/thermal systems for carbon dioxide mitigation applications: a review - Kazem, Hussein A.; Al-Waeli, Ali H. A.; Chaichan, Miqdam T.; Alnaser, Waheeb E. (Frontiers in Built Environment, 2023)
The urgent need to mitigate carbon dioxide (CO2) emissions and address climate change has led to increasing interest in renewable energy technologies. There are other promising energy generation systems, including photovoltaic/thermal (PV/T) systems. This paper provides a comprehensive review of PV/T systems for CO2 mitigation applications. PV/T systems are reviewed according to their principles, their design configurations, and their performance characteristics. Various types of PV/T systems, including flat-plate, concentrating, hybrid, and novel designs, are discussed, along with their advantages and limitations. In addition to examining PV/T systems as part of the integration of building systems with renewable energy sources and energy storage technologies. Furthermore, the environmental and economic aspects of PV/T systems, as well as their potential for CO2 mitigation in various applications such as residential, commercial, industrial, and agricultural sectors, are critically analyzed. Finally, future research directions and challenges in the field of PV/T systems for CO2 mitigation are outlined. The purpose of this review is to provide researchers, policymakers, and practitioners with information on how PV/T systems can be applied to reduce CO2 emissions and promote sustainable building design.